Evaluation of Strategic and Marketing Indicators in Supply Chain with Multi-Criteria Decision-Making Method - Moshki Kashi, Maryam (International journal of industrial engineering and operational research, 2024)
Effective strategic management and supply chain management hinge on the evaluation of strategic and marketing indicators. However, the presence of multiple, often conflicting, criteria make decision-making a complex challenge. This paper explores the application of Multi-Criteria Decision-Making (MCDM) methods in evaluating these indicators within a supply chain context. The literature review examines various MCDM techniques, highlighting their strengths and weaknesses in supply chain applications. The methodology section details the framework for indicator evaluation using an MCDM approach. A hypothetical case study demonstrates the implementation with numerical results. Finally, the conclusion summarizes the findings, discusses limitations, and suggests avenues for future research.